Publics and counter-publics of net-zero - Valenzuela, JM; Lezaun, J (Elsevier, 2024)
The proliferation of pledges to reach net-zero emissions has revealed a wide range of understandings of what such a pledge entails. The lack of international standards to define decarbonisation pathways and the many kinds of speculative offsets available for net-zero calculations have generated a multiplication of public commitments not tethered to any specific mechanism of accountability. Many have criticised this state of affairs as a governance vacuum allowing extravagant forms of ‘greenwashing,’ with corporations and countries asserting ostensibly ambitious goals without adopting verifiable instruments for their delivery. This paper addresses the situation from a slightly different perspective, exploring instead how net-zero pledges create new climate publics and counter-publics. Drawing on three case studies (UK national net-zero policy, the Race to Zero campaign, and the Science Based Targets Initiative), and informed by a pragmatist understanding of ‘public’ and ‘public formation,’ we examine how the adoption of a formal but ambiguous target leads to a collective consideration of consequences, thus expanding the range of actors engaged in disputes over alternative climate futures.